Una finestra sul mondo del lavoro The labor law that helps young people, in simple words. - AA.VV (Ledizioni, 2015)
This volume's purpose is making standards of basic employment law, accessible to everybody, even to non-lawyers. This book is part of the "Una finestra sul mondo del lavoro" project of University of Milano - Bicocca. The project is promoted by the Students' Association of Bicocca and the Left Wing List. This book is part of the "A window on the world of work" project of University of Milano - Bicocca. The project is promoted by the Students' Association of Bicocca and the Left Wing List. Within this project, graduate students of the Faculty of Law, practitioners and young lawyers specialized in employment law, have joined their skills to create a platform of labour law training for students. This work does not aim to academically and comprehensively treat these subjects: it is rather moved by the spirit of giving to all, non-lawyers as well, the ability to access the raw information to understand the regulation of their employment contract.